Failure process in glass fiber reinforced polymer matrix composites subjected to different tensile loading conditions - 377919 Mohd. Rasyidi Ridzuan (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2006